A male figure surrounded by dancers and musicians - Temples of India Project Team (Jio Institute, 2024)
A male figure surrounded by dancers and musicians is framed in panels with pillars and tiered shikhara with gavaksha (horseshoe) motifs. Their faces are defaced. The male figure is wearing a necklace with a pendant and other heavy jewellery. He sports an elaborate coiffure tied with a band in front, indicating he may be a royal figure. A central male figure is seated in the lalitasana pose on a circular raised seat, in the company of musicians and dancers. Two female dancers are balancing themselves on big drums on either side of the male figure. Small figures of musicians are holding the base of the drums. The one on the left is playing the flute. Four small figures appear at the top, playing cymbals, two on either side of the male figure. The cymbal players are suspended from trees in the background, very close to the female dancers.